Synthesis, Characterization and Spectral Studies of Azo Dyes Ligands Complexes with Some Metal Ions and Their Industrial and Bacterial Application - Wedian Mansor Obaid (Journal of Global Pharma Technology, 2016)
1-[4-(4-Acetyl-2-hydroxy-phenylazo)-phenyl]-ethanone (HL1) and1-[3-Hydroxy-4(4-nitro-phenylazo)-phenyl]-ethanone (HL2) were produced by combination the diazonium salts of amines with 3-hydroxyacetophenone. (C.H.N) analyses, FT-IR, UV-Vis, 1H and 13CNMR spectral are use to identified for the ligands. Complexes for Zn+2,Cd+2 and Hg+2 were prepared as well specified through using atomic absorption of flame, analysis of elements, spectral methods also conductivity quantification. The nature of production complexes were studied continued mole ratio as well continued variance ways, Beer's law followed over condensation scope (1×10-4- 3×10-4)M. High molar absorption for compound solutions have been noticed. Analytical datum showed that in every the complexes offered 1:2 metal-ligand ratios. Depending physicochemical data a tetrahedral geometry were described of the metal chelates. Biological efficacy from compounds has been tested. Other than, dyeing completed of the produced compounds has been workable on fabric of cotton.Keywords: Complexes, azo dyes, microbial activity, dyeing.